Gastroenteropancreatic neuroendocrine neoplasms: epidemiology, genetics, and treatment - Tan, Baizhou; Zhang, Beiyu; Chen, Hongping (Frontiers in Endocrinology, 2024)
The incidence of gastroenteropancreatic neuroendocrine neoplasms (GEP NEN) is increasing at a rapid pace and is becoming an increasingly important consideration in clinical care. Epidemiological data from multiple countries indicate that the incidence of gastroenteropancreatic neuroendocrine neoplasms (GEP NEN) exhibits regional, site-specific, and gender-based variations. While the genetics and pathogenesis of some GEP NEN, particularly pancreatic NENs, have been investigated, there are still many mechanisms that require further investigation. The management of GEP NEN is diverse, but surgery remains the primary option for most cases. Peptide receptor radionuclide therapy (PRRT) is an effective treatment, and several clinical trials are exploring the potential of immunotherapy and targeted therapy, as well as combination therapy.